Realitas Sosial Kehidupan Generasi Milenial Dalam Novel Seporsi Mie Ayam Sebelum Mati Karya Brian Khrisna: Kajian Sosiologi Sastra Alan Swingewood - Dewi Nur Afifah; Hespi Septiana (CV. SINAR HOWUHOWU, 2026)
This study aims to describe the relationship between the narrative of mental health disorders experienced by the main character and the life phenomena of the current millennial generation. The theory used in this study is literary sociologist Alan Swingewood who views that to understand literary works in their entirety is not only based on internal elements, but must also be associated with external factors to explore the meaning implicit in a literary work. These external factors will make it easier to understand the historical background, culture, social conditions of people's lives, and the psychology of the author that influenced the creation of the work. Thus, this study focuses on three main problems, namely (1) the triggering factors for the main character to experience acute depression, (2) the relationship of the novel narrative regarding the form of depression in the main character with the current phenomenon, and (3) the main criticism of the author as the background for the creation of the novel. Based on these three problems, this study uses a qualitative descriptive method with collection techniques in the form of reading and taking notes. In addition, the analysis of data findings from the research object is through the stages of data reduction, data presentation, and conclusion drawn. The results of the study show that the triggering factors for the main character experience acute depression due to social pressure, existential crisis, and social alienation. In addition, the narrative in the novel also shows the connection between the problems of the current millennial generation which is portrayed through the main character who experiences forms of depression in the form of loneliness, resignation, despair, and disappointment. Through the form of depression described by the author as complex in the main character, the presentation of mental health issues in the novel Seporsi Mie Ayam Before Death by Brian Khrisna highlights the standardization of happiness created by the surrounding environment as the background for the creation of the novel.